Future Challenge of the Freedom of Religion Act: Comparing Indonesia and Malaysia - Naefi, Mohammad (Semarang State University Undergraduate Law and Society Review, 2021)
Indonesia is one of the countries that uphold human rights International one of the examples is the freedom of religion or embrace religion. It is proven by the inclusion of one of the international human rights values ​​into our constitution namely article 28 I paragraph (1) of the 1945 Constitution. As a sovereign country, Indonesia is obliged to protect the right of its citizens to embrace the religion or belief adopted without any compulsion from any party. Every citizen has the freedom to determine his or her faith or belief according to the mind and conscience of each. So Human Rights are rights that protect us to live together in society without any disturbance. The right to freedom of religion becomes important issue. This study aims to analyze and describe the freedom of religious act in Indonesia and Malaysia in the perspective of human rights.